A discourse analysis of Galatians and the new perspective on Paul - Yoon, David I. (Leiden Boston Brill, 2019)
Front Matter -- Copyright page -- Preface -- Acknowledgements -- Figures and Tables -- Abbreviations -- Theory -- An Introduction to the New Perspective on Paul -- A Definition and Survey of Discourse Analysis -- Introduction to SFL Discourse Analysis with Reference to Register -- Analysis -- Mode Analysis of Galatians -- Field Analysis of Galatians -- Tenor Analysis of Galatians -- A Summary and a Contextual Configuration of Paul’s Letter to the Galatians -- Back Matter -- Thematization in Galatians -- Transitivity Network in Galatians -- Speech Functions in Galatians -- Bibliography -- Index of Modern Authors -- Index of Ancient Sources.
In A Discourse Analysis of Galatians and the New Perspective on Paul , David I. Yoon outlines discourse analysis from the framework of Systemic Functional Linguistics for analyzing Paul’s letter to the Galatians. From this analysis, he determines whether the context of situation better reflects the New Perspective on Paul, covenantal nomism, or a more traditional perspective, legalism. The first half of the book introduces the New Perspective on Paul and discourse analysis, followed by a detailed model of SFL discourse analysis with respect to register and context of situation. The second half is a discourse analysis of Galatians. This is the first monograph-length study to address the New Perspective on Paul from a linguistic approach, and will as such be of great interest to scholars of Pauline Studies, linguistics, and theology
Keywords: Bible -- Language, style; Bible -- Criticism, interpretation, etc; Discourse Analysis; Greek language, Biblical -- Discourse analysis; Bibel; Textanalyse; Hochschulschrift